PENGARUH VIRAL MARKETING, ONLINE CONSUMER REVIEWS, HARGA, DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI TOKOPEDIA - Jihan Najwah; Amalia Nur Chasanah (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
ABSTRACTIn modern times, the internet has been considered as a necessity for many people. The use of the internet has changed consumer behavior from direct purchases in stores to online purchases. Online shopping makes it easy for consumers to shop without spending a lot of time and effort in stores. In addition to the convenience obtained in online shopping, it is important to have a marketing strategy in selling online, namely viral marketing, online consumer reviews, prices, and brand ambassadors. This study aims to determine the effect of viral marketing, online consumer reviews, prices, and brand ambassadors on online purchasing decisions at Tokopedia. The population of this research is all Tokopedia users in Indonesia. The method used is a quantitative method with data collection using purposive sampling which is distributed through a questionnaire on google form to 220 respondents. The data has been processed using multiple linear regression, validity and reliability tests, classical assumption tests, and hypothesis testing. The results show that: (1) Viral Marketing has a significant and positive influence on online purchasing decisions at Tokopedia (2) Online Consumer Reviews have a significant and positive influence on online purchasing decisions at Tokopedia (3) Price has a significant and positive influence on online purchasing decisions at Tokopedia (4) Brand Ambassadors have a significant and positive influence on online purchasing decisions at Tokopedia.Keywords: viral marketing, online consumer reviews, price, brand ambassador